Association between oxidative balance score and skeletal muscle mass and strength: NHANES from 2011 to 2018 - Zhao, Xiaoxuan; Hua, Lijiangshan; Jin, Kaili; Sun, Qiuhua; Wang, Rongyun (Frontiers in Nutrition, 2024)
Objective: Oxidative stress is a risk factor for sarcopenia. The Oxidative Balance Score (OBS) is a widely employed tool for evaluating the oxidative stress-related exposures from dietary and lifestyle factors. In this study, we aimed to conducted to explore the relationship between OBS and skeletal muscle mass and strength. Methods: 6438 subjects from 2011-2018 and 5414 from 2011-2014 from the National Health and Nutrition Examination Survey (NHANES) were selected for analysis. The correlations between OBS and skeletal muscle mass and handgrip strength were investigated using multivariate logistic regression and linear regression analysis. Results: Compared with lowest OBS, participants with OBS in the highest quartile had lower risk of low skeletal muscle mass (OR=0.173 (0.120~0.248), p<0.0001) and low handgrip strength (β=0.173 (0.120~0.248), p=0.011). The negative association also were found between dietary/lifestyle OBS and skeletal muscle mass (OR=0.268 (0.178~0.404), P<0.0001; OR=0.231 (0.130~0.410), p<0.0001) and handgrip strength (β=1.812 (0.555~3.071), P=0.008; β=-2.255 (-3.430~ -1.079), p<0.001) independently. The positive association remains significant, especially among men and those with higher education levels by subgroup analysis. Conclusions: All of these results indicated a negative association between OBS and low skeletal muscle mass and handgrip strength. An antioxidant-rich diet and healthy lifestyle are crucial for enhancing skeletal muscle mass and strength.